The Effect of Rinsing, Soaking and Cooking Method on Level of Lead and Cadmium in Consumed Rice in Iran: A Systematic Review and Meta-analysis - Niloofar Moshfeg; Azam Abbasi; Enayat Berizi (Journal of Health Sciences and Surveillance System)
Background: Considering the high levels of heavy metals in Iranian rice, it is required to take measures to reduce them. One of these measures is to soak or rinse the rice before cooking, which is done in two ways in Iranian cuisine: Kateh (traditional) and Pilaw.Methods: This systematic review and meta-analysis aimed to find the best Iranian rice recipe for reducing Cadmium (Cd) and Lead (Pb) and compare the levels of these metals in Iranian and imported rice consumed in Iran. In this study the data were found from international and national databases from 2002 to 2022. 66 non-duplicate articles were found, eight review articles, and 47 unrelated articles were removed. The remaining 11 eligible articles were studied in terms of the types of heavy metals. Considering that Pb and Cd were investigated in most of the articles, these two metals were considered for this research. Begg’s test was used to check the risk of bias.Results: A t otal of 7 a rticles w ere fi nally s elected, a nd t he information was analyzed in Stata software. Based on Begg’s test, no sign of publication bias was found. According to the results, Pb levels decreased in cooking methods compared to Cd, and their average reached 0.00 mg/kg. Also, the results showed that soaking or rinsing raw rice before cooking reduced Cd and Pb levels in the Pilaw method more than in the Kateh method (except for two exceptions).Conclusion: Based on this study, it is preferable to avoid importing low-quality rice with high levels of heavy metals. Also, more attention should be paid to rice cultivation in Iran to reduce the concentrations of these metals and, to reduce heavy metals, the best method is to soak the rice for a few hours before cooking, discard the water and cook it using the Pilaw method.